Births in Italy: a neonatologist's view - Rino Agostiniani (Hygeia Press di Corridori Marinella, 2015)
The complexity of care needs that characterize economically advanced societies requires a systemic approach to the organization of health services so as to enable them to meet the diverse health needs of the population, in line with their economic sustainability. The proper functioning of the service network is related to the ability to change our way of thinking and to the development of health services by adapting them to the rapid and profound changes characterizing the social fabric. The current organization of the maternity facilities network in Italy shows strong regional differences and raises many concerns when we analyze the data in the tenth Report on Births in Italy, prepared by the Statistics Office with 2011 data from the information flow of the Certificate of Attendance at Childbirth (CeDAP). This survey is the richest national source of health, epidemiological, and socio-demographic information on births, and therefore represents a very important tool for health planning, at both a national and, especially, a regional level   Proceedings of the 11th International Workshop on Neonatology and Satellite Meetings · Cagliari (Italy) · October 26th-31st, 2015 · From the womb to the adult Guest Editors: Vassilios Fanos (Cagliari, Italy), Michele Mussap (Genoa, Italy), Antonio Del Vecchio (Bari, Italy), Bo Sun (Shanghai, China), Dorret I. Boomsma (Amsterdam, the Netherlands), Gavino Faa (Cagliari, Italy), Antonio Giordano (Philadelphia, USA) .